2020
DOI: 10.1111/cfs.12795
|View full text |Cite
|
Sign up to set email alerts
|

Children living with parental substance misuse: A cross‐sectional profile of children and families referred to children's social care

Abstract: Parental substance misuse is a significant public health and children's rights issue. In the United Kingdom, social workers frequently work with children and families affected by substance misuse. However, relatively little is known about this population, particularly at point of referral to children's social care. This paper reports on the largest known study of parental substance misuse as a feature of children's social care work in England. The paper provides a cross-sectional profile of 299 children living… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…At point of the index referral, children's ages ranged from unborn to 17 years (Mdn = 6, Mean = 6.4). Full descriptive details of the sample are available in Roy (2021). Every child in the sample had at least one episode of involvement with CSC.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…At point of the index referral, children's ages ranged from unborn to 17 years (Mdn = 6, Mean = 6.4). Full descriptive details of the sample are available in Roy (2021). Every child in the sample had at least one episode of involvement with CSC.…”
Section: Resultsmentioning
confidence: 99%
“…This ESRC funded study was a retrospective longitudinal cohort study of 299 children all living with PSM and all referred to CSC in one local authority in England between March-July 2012. Further detail on methods can be found in (Roy, 2018(Roy, , 2021. Quantitative and qualitative data were collected from social work case files about each child.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This severely limits understand of the issues and the possibility of developing tailor-made services that recognize the interconnections and complexity of the issues. The largest, and most recent profiling of cases involving parental substance misuse in an English local authority, found that of the 299 children referred to children's social care, 42.8% were also exposed to DA ( 57 ). Risk, or actual abuse and neglect, were the most frequent reasons for referral.…”
Section: What Is Known About the Inter-relationship Between Parental ...mentioning
confidence: 99%